Effectiveness of picture exchange communication system in developing requesting skills for children with multiple disabilities - Alfuraih, Riyadh Khalid; Almalki, Nabil Sharaf; AlNemary, Faisal Mohammed (Frontiers in Psychology, 2024)
This study evaluated the effectiveness of the Picture Exchange Communication System (PECS) in developing and generalizing requesting skills among children with multiple disabilities. The study was conducted at The Autism Center of Excellence, Riyadh, Saudi Arabia. This study included three participants age ranged from 4.5 to 6.5 years with intelligence quotient (IQ) scores ranging from 40 to 44. All participants were inrolled in Inclusive Education program. A training program based on PECS was implemented, and data collection involved recording participant responses and observations by external observers. The study followed an experimental approach, specifically utilizing Single-Subject Design (SSD) with a focus on Multi-Baseline Designs (MBD). The results of the study indicated that PECS facilitated the development of requesting skills in children with multiple disabilities, promoting skill retention and generalization across similar situations.